Strategic Planning 4.8 [document]
CSUCI shares data with the campus community in multiple forums. Some more formal than others, there is an appropriate venue for each member of the campus to engage in providing feedback and input to ongoing strategic planning. This allows for breadth of engagement as well as depth.